PELATIHAN GURU SEKOLAH DASAR DALAM PENGGUNAAN APLIKASI PERSENTASI POWTOON DAN SPARACOL - Achmad Fathoni; Ajib Rosyadi; Indra Gunawan; Muhamad Taufik Hidayat (STMIK Royal, 2020)
Abstract: The purpose of this social service is to provide learning media training based on the presentation application, Sparcol and Powtoon. This activity was given to teachers in Elementary School 9 Purwodadi. The social service session consists of installing an application, creating an account, adding images and text, changing the background, and saving the results that have been made. The model used is a workshop model with lectures, demonstrations, question and answer and direct practice methods. Evaluation is done by distributing information and motivation questionnaires to participants and product checklists. In general, participants claimed that the training schedule was right, the time sharing (lectures, demonstrations, question-answer and direct practice) was also felt positively by the participants. Participants are satisfied with the topic presented and feel that most of the expectations and objectives of the social service are fulfilled. Evaluation results indicate that the material delivered can be followed well.Keyword: Powtoon Training, Sparcol Training, Elementary School Abstrak: Tujuan dari pengabdian ini adalah memberikan pelatihan media pembelajaran berbasis aplikasi presentasi Sparcol dan Powtoon. Kegiatan pengabdian ini diberikan kepada guru-guru SD Negeri 9 Purwodadi. Sesi pengabdian terdiri dari instal aplikasi, membuat akun, menambah gambar dan teks, merubah background, dan menyimpan hasil yang telah dibuat. Model yang digunakan adalah model lokakarya dengan ceramah, demonstrasi, tanya jawab dan metode praktik langsung. Evaluasi dilakukan dengan menyebarkan angket informasi dan motivasi kepada peserta dan daftar periksa produk. Secara umum, peserta mengklaim bahwa jadwal pelatihan sudah tepat, pembagian waktu (ceramah, demonstrasi, tanya jawab dan praktik langsung) juga dirasakan positif oleh peserta. Peserta puas dengan topik yang disajikan dan merasa bahwa sebagian besar harapan dan tujuan pengabdian terpenuhi. Hasil evaluasi menunjukkan bahwa materi yang disampaikan dapat diikuti dengan baik. Kata Kunci: Pelatihan Powtoon, Pelatihan Sparcol, Sekolah Dasar